Time rationalities: Complementing “the orientation from the present” and the focus on “short” and “long terms” in performance measurement - Terhi Chakhovich (Emerald, 2022)
Purpose – The temporality of performance measurement systems has been claimed to affect actors’ time orientation, such as that of listed company managers. This study explores that view.
Design/methodology/approach – The study uses constructivist data gathered from executives in one listed and one non-listed company.
Findings – The study shows that the research on performance measurement is based on a linear-quantitative view on time that assumes that humans orient towards the future from one point, the present; this view excludes other time-related constructs, particularly the past, and highlights a choice between the short term and the long term, idealising the long term. It is shown that the performance measurement of non-listed company executives is constructed through (1) past-based, (2) present-based and (3) future-based rationalities: executives acknowledge (1) the past as a basis for present and future performance, (2) present actions as shaping future performance and (3) future plans and performance targets as bases for present actions. Listed company executives’ performance measurement is constructed predominantly through the present-based time rationality.
Research implications – “The orientation from the present” and the “short” and “long terms” could be enhanced with time rationalities.
Practical implications – The evaluation periods within performance measurement systems do not determine the time orientations of the actors subjected to those systems; time rationalities could be considered when designing such systems.
Originality/value – The paper provides a novel view on performance measurement and time.